A study on profile of patients using inhalants attending in a tertiary care center of East India - Debshankar Mukhopadhyay; Abhijit Chakraborty; Srijit Ghosh (Asian Journal of Medical Sciences, 2022)
Background: There is a slow but steady increase in inhalant use in India among adolescent age group. There is a very few studies regarding inhalant use disorder in India. No study has been reported from West Bengal. Aims and Objectives: In our study, we aimed to study the sociodemographic and clinical profile of patients using inhalants. Materials and Methods: A cross-sectional clinic-based study conducted in a tertiary care center medical college hospital of West Bengal. All patients attending in the outpatient department with a history of inhalant use were taken in this study irrespective of diagnosis and purpose of visit. Duration of the study was 18 months. Sociodemographic and clinical profiles were obtained using a semi-structured pro forma. Results: We studied 26 patients. All were unmarried male from urban background, middle to lower socioeconomic status. Most of them were from nuclear family. Mean age was 15.2 years. Most of them were studying (69.2%). Inhalant was the preferred substance for all of them. Tobacco was the most common substance used along with inhalants. The most common inhalants substance was glue (Dendrite) 84.6%. Sniffing (80.8%) was the most common form of inhalation. For all of the patients, inhalation was out of curiosity. Only 23.1% had a positive family history of substance dependence. The most common comorbidity found was conduct disorder (30.8%). Motivation for quitting was poor for most of the patients. Conclusion: Inhalant use disorder is an important but still unexplored research area in West Bengal. Although not common, inhalant use disorder is not rare in clinical setting.